Perencanaan Struktur Gedung Rumah Susun 4 Lantai Dengan Sistem Rangka Pemikul Momen Biasa (SRPMB) di Wilayah Wonogiri - Aji, Dani Sapto, Ir. Ali Asroni, S.T., M.T, Muhammad Ujianto, S.T., M.T (2016)
Wonogiri is a growing area with the improvement of infrastructure, tourism and business as a whole to meet the demands of development in Indonesia making residential needs increase. Construction of flats is one of the solutions with the land use that is not too big into residential center with modern design can attract the interest of consumers, so the flats is not only memorable as residential relocation of slum and sober. Therefore, it will be planned 4 floors with Ordinary Moment Resisiting Frames (OMRF). Planning flats refers to the regulations (SNI) has published the latest government, namely SNI 1726-2012 (the rules of building structure earthquake for building structure and non-structure) and SNI 2847-2013 (requirenment of concrete structural for building structure). Planning flats include steel truss roof structure, beams, columns, roof slabs, slabs, foundations and sloof. Location flats are in Wonogiri with the classification of land sites including category SC (hard soil), earthquake resistant building with the response modification factor (R) amounted to 3, the primacy factor buildings Ie with a value of 1,0. Concrete quality used f'c 20 MPa, steel reinforcement for longitudinal bars fy = 350 MPa and confinement bars fyt = 300 MPa. This planning using SAP2000 program assistance for structural analysis calculations and AutoCad program for drawing details of the building structure. The results of planning for the roof steel frame using BJ37, roof slab with a thickness 10 cm and a thick slab with 12 cm, beam structure with dimensions 400/600 mm and 250/400 mm. For column with dimensions 450/600 mm. For bottom structures using continuous foundation depth of -1.60 m with soil bearing capacity = 150 kPa.